Meningkatkan Keterampilan Sosial Siswa dengan Menerapkan Model Pembelajaran Berbasis Masalah - Gunawan, Putu Agus; Indrayani, Luh (Universitas Pendidikan Ganesha, 2021)
This study aims to see the improvement of social skills of 8 B3 grade students of SMPN 4 Singaraja using a problem-based learning model in social studies learning. This research was conducted at SMPN 4 Singaraja, using 36 students as the subject of grade 8B3. The object of this research is the students' social skills. The approach used in this research is a quantitative approach. Data collection used questionnaires and interviews, with social skills instruments grid instruments and interview sheets. From the results of data analysis, the application of the Problem Based Learning model in Social Sciences learning can improve the social skills of grade 8 B3 students of SMPN 4 Singaraja. This statement can be proven by the results of the study which showed that the average score of social skills of grade 8 B3 students was 76%. This achievement has increased by 12% with the initial condition of 64%. The average score of students' social skills in class 8B3 was 84%. This achievement has increased by 8% with the initial condition of 76%.